Synthesis, characterization and biological activity of a new long-chain imine ligand and some transition metal complexes in solvent-free conditions - Elmali, Fikriye Tuncel; Sutay, Berkay; Ozbek, Berna; Demirhan, Nebahat (IOS PRESS, 2012)
A new N-alkyl long-chain alkyl imine ligand (N-dodecyl-N1-dacanimine) has been synthesized by the reaction of dodecylamine (laurylamine) with decanal in molar 1 : 1 ratio and its Cu(I), Cu(II), Ni(II) and Co(II) complexes have been prepared under solvent-free conditions. The newly synthesized compounds have been verified by FTIR, UV-vis. and mass spectra. All of the compounds were tested for antimicrobial activity against Staphylococcus aureus ATCC 6538, meticillin resistant Staphylococcus aureus (MRSA) ATCC 33591, Staphylococcus epidermidis ATCC 12228, Escherichia coli ATCC 8739, Klebsiella pneumoniae ATCC 4352, Pseudomonas aeruginosa ATCC 1539, Proteus mirabilis ATCC 14153 and the yeast, Candida albicans ATCC 10231. Among the compounds, the ligand was found the most active compound against all strains. The Cu(II) complex exhibited very strong antibacterial activity against bacteria except for Pseudomonas aeruginosa ATCC 1539, Proteus mirabilis ATCC 14153. Also, all compounds showed very strong antifungal effects against C. albicans ATCC 10231.
Keywords: Complex; imine; solvent-free condition; biological activity; Chemistry